2013
DOI: 10.1177/1477370813512584
|View full text |Cite
|
Sign up to set email alerts
|

Keeping delinquency at bay: The role of the school context for impulsive and sensation-seeking adolescents

Abstract: Previous research shows that a disadvantaged school setting is associated with increased risk of adolescent delinquency. However, there is limited research on individual differences in such contextual effects. In this study, we investigated whether the association between impulsive and sensation-seeking traits and delinquency is modified by the school setting, focusing on schools' socioeconomic and ethnic composition and average school performance. We also examined whether the association between gender and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…Only 4 items were used to capture delinquent behaviors. However, sensitivity analyses, including a wider range of delinquent behaviors, as well as other studies based on the same data, do suggest that our findings are robust despite the few indicators used …”
Section: Discussionsupporting
confidence: 59%
“…Only 4 items were used to capture delinquent behaviors. However, sensitivity analyses, including a wider range of delinquent behaviors, as well as other studies based on the same data, do suggest that our findings are robust despite the few indicators used …”
Section: Discussionsupporting
confidence: 59%
“…Additionally, some empirical research results have confirmed that sensation seeking amplifies the risk effect of school adversity on adolescent risk behaviors. For instance, Eklund and Fritzell (2014) found that the interaction of sensation-seeking with negative school effects was associated with an increased risk of adolescents’ delinquent behaviors. Moreover, some empirical research has confirmed that high sensation seeking could significantly aggravate the detrimental effects of the consequences of low school engagement (e.g., substance abuse) on adolescent self-injurious thoughts and behaviors ( Ortin et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the influence of for instance, unfavorable home conditions may be conditional on the characteristics of the school setting in question (Wilcox, 2003). Yet, although some recent studies suggest that such interacting effects are important (Crosnoe, 2004;Eklund & Fritzell, 2013;Olsson & Fritzell, 2017), most research conducted on school effects has concerned the direct effects of schools on student outcomes. However, considering the compensatory duty of the school (Granvik Saminathen et al, 2018;Skolverket, 2012), the most important role of schools may be the potential they hold for moderating the effects of individual-level differences (micro-macro interactions) (Wilcox, 2003).…”
Section: Introductionmentioning
confidence: 99%